A rare single nucleotide variant in Pm5e confers powdery mildew resistance in common wheat. Issue 3 (26th July 2020) - Xie, Jingzhong; Guo, Guanghao; Wang, Yong; Hu, Tiezhu; Wang, Lili; Li, Jingting; Qiu, Dan; Li, Yahui; Wu, Qiuhong; Lu, Ping; Chen, Yongxing; Dong, Lingli; et al.
Summary: Powdery mildew poses severe threats to wheat production. The most sustainable way to control this disease is through planting resistant cultivars. We report the map‐based cloning of the powdery mildew resistance allele Pm5e from a Chinese wheat landrace. We applied a two‐step bulked segregant RNA sequencing (BSR‐Seq) approach in developing tightly linked or co‐segregating markers to Pm5e . The first BSR‐Seq used phenotypically contrasting bulks of recombinant inbred lines (RILs) to identify Pm5e ‐linked markers. The second BSR‐Seq utilized bulks of genetic recombinants screened from a fine‐mapping population to precisely quantify the associated genomic variation in the mapping interval, and identified the Pm5e candidate genes. The function of Pm5e was validated by transgenic assay, loss‐of‐function mutants and haplotype association analysis. Pm5e encodes a nucleotide‐binding domain leucine‐rich‐repeat‐containing (NLR) protein. A rare nonsynonymous single nucleotide variant (SNV) within the C‐terminal leucine rich repeat (LRR) domain is responsible for the gain of powdery mildew resistance function of Pm5e, an allele endemic to wheat landraces of Shaanxi province of China. Results from this study demonstrate the value of landraces in discovering useful genes for modern wheat breeding. The key SNV associated with powdery mildew resistance will be useful for marker‐assisted selection of Pm5e in wheat breeding programs.